Late Reporting Among Newly Registered Patients for Anti-Retroviral Therapy in A Central District Ujjain, India - Khandelwal, Vidit; Sabde, Yogesh D; Pradhan, Riddhi; Sathsh, Mehta Chandra (National Journal of Community Medicine, 2013)
Introduction: Current trends in HIV/AIDS epidemic demand quality and sustainable programs to provide universal access to antiretroviral therapy (ART). The inherent disparities in population subgroups result in changing profiles of ART beneficiaries which are needed to account for with reference to regional findings. Present study aims to explore the socio demographic and clinical profile of the patients reporting at an ART central in central India. Methods: Facility based cross sectional study at an ART center in a tertiary care hospital in Ujjain district of central India. The study included all newly registered people living with HIV/AIDS (PLHA) over 18 years of age, during one year period. Results: The study reports findings of 297 participants. Majority of the patients belonged to poorer socioeconomic strata. The representation of women and people from rural areas was lesser than expected. One third PLHA came late in the course of disease (stage III and IV). The average haemoglobin level (9.6gm%) and weight (45.4Kg) of the PLHA indicated their poor nutritional status. Conclusion: Late reporting at the initiation of ART was reported in about one third of the patients which could adversely affect effectiveness of ART. Efforts to investigate lesser representation of women and rural people are indicated. The study raised concerns about the possible routes of transmission need more investigation.